2013
DOI: 10.1088/0957-4484/24/50/505307
|View full text |Cite
|
Sign up to set email alerts
|

Large-area, continuous roll-to-roll nanoimprinting with PFPE composite molds

Abstract: Successful implementation of a high-speed roll-to-roll nanoimprinting technique for continuous manufacturing of electronic devices has been hindered due to lack of simple substrate preparation steps, as well as lack of durable and long lasting molds that can faithfully replicate nanofeatures with high fidelity over hundreds of imprinting cycles. In this work, we demonstrate large-area high-speed continuous roll-to-roll nanoimprinting of 1D and 2D micron to sub-100 nm features on flexible substrate using perflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 31 publications
0
57
0
Order By: Relevance
“…[ 27 ] SEM images were taken using JEOL JSM -7001F SEM. The palladium electrodes were deposited using shadow masks in an AJA International Orion 8 sputtering system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 27 ] SEM images were taken using JEOL JSM -7001F SEM. The palladium electrodes were deposited using shadow masks in an AJA International Orion 8 sputtering system.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24][25][26] Recently, we demonstrated large-area continuous roll-to-roll nanoimprinting of 1D and 2D micrometer to sub-100 nm features on fl exible substrate using perfl uoropolyether (PFPE) hybrid molds on a custom designed roll-toroll nanoimprinter. [ 27 ] R2RNIL is a platform process technology that can be adapted to a wide range of applications including fl at panel displays, [ 28,29 ] biomedical devices, [ 30 ] fl exible solar cells and antirefl ective coatings for solar cells. [ 31 ] But the full potential of R2R NIL fabrication has can be applied to other areas such as the fabrication of physical, chemical and biological sensors etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV-NIL is a rapid nanofabrication technique and has been used for large-area and high-throughput fabrication. 18,19 A suitable liquid must remain in contact with a UV-transparent patterned template for UV-NIL. The separation process may result in substantial damage to the resist or the template if adhesion is high.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Among the various printing techniques, such as micro-contact printing [13], nanoimprinting [14], screen printing [15], stencil printing [16,17], drop-on-demand inkjet printing [18] and roll-toroll printing [19], direct additive printing has many advantages such as low cost and easy operation compared with the conventional vacuum deposition and photolithographic patterning methods [20]. In recent years, Russo et al [21] demonstrated a facile pen-on-paper method to directly create flexible printed electronics using conductive silver ink.…”
Section: Introductionmentioning
confidence: 99%